Carbon o-Electron Densities and C-H Stretching Vibration Frequencies of Phenanthrene - Kubba, Rehab; Al-ani, Raghida; Shanshal, Muthana (Iraqi Journal of Science, 2025)
MINDO/3-FORCES calculations were carried out for the vibration frequencies and IR absorption intensities of phenanthrene radical fons. The obtained frequency values were compared with the experimental values when possible. It was found that the C-H stretobing frequencies are directly related to the carbon a-electron densities of the relevant atoms